Fosfomycin Protects Mice From Staphylococcus aureus Pneumonia Caused by α-Hemolysin in Extracellular Vesicles by Inhibiting MAPK-Regulated NLRP3 Inflammasomes - An, Yanan; Wang, Yang; Zhan, Jiuyu; Tang, Xudong; Shen, Keshu; Shen, Fengge; Wang, Chao; Luan, Wenjing; Wang, Xuefei; Wang, Xueyan; Liu, Mingyuan; Zheng, Qingchuan; et al. (Frontiers in Cellular and Infection Microbiology, 2019)
α-Hemolysin (Hla) is a significant virulence factor in Staphylococcus aureus (S. aureus)-caused infectious diseases such as pneumonia. Thus, to prevent the production of Hla when treating S. aureus infection, it is necessary to choose an antibiotic with good antibacterial activity and effect. In our study, we observed that Fosfomycin (FOM) at a sub-inhibitory concentration inhibited expression of Hla. Molecular dynamics demonstrated that FOM bound to the binding sites LYS 154 and ASP 108 of Hla, potentially inhibiting Hla. Furthermore, we verified that staphylococcal membrane-derived vesicles (SMVs) contain Hla and that FOM treatment significantly reduced the production of SMVs and Hla. Based on our pharmacological inhibition analysis, ERK and p38 activated NLRP3 inflammasomes. Moreover, FOM inhibited expression of MAPKs and NLRP3 inflammasome-related proteins in S. aureus as well as SMV-infected human macrophages (MΦ) and alveolar epithelial cells. In vivo, SMVs isolated from S. aureus DU1090 (an isogenic Hla deletion mutant) or the strain itself caused weaker inflammation than that of its parent strain 8325-4. FOM also significantly reduced the phosphorylation levels of ERK and P38 and expression of NLRP3 inflammasome-related proteins. In addition, FOM decreased MPO activity, pulmonary vascular permeability and edema formation in the lungs of mice with S. aureus-caused pneumonia. Taken together, these data indicate that FOM exerts protective effects against S. aureus infection in vitro and in vivo by inhibiting Hla in SMVs and blocking ERK/P38-mediated NLRP3 inflammasome activation by Hla.